The Herd Health Handbook for Goat Producers: Biosecurity at the Farm Level - Ray Mobley; Carmen Lyttle-N’guessan (EDIS)
FAMU006, a 20-page illustrated fact sheet by Ray Mobely and Carmen Lyttle-N'guessan, describes aspects of an effective bio-security program, bio-security measures, food safety concerns, and how HACCP works. Includes references and an appendix listing disease symptoms, possible treatments, and examples of treatment records. Published by the Florida A & M University Extension, September 2009.